Comparison between the Gen-Probe Transcription-Mediated Amplification Trichomonas vaginalis Research Assay and Real-Time PCR for Trichomonas vaginalis Detection Using a Roche LightCycler Instrument with Female Self-Obtained Vaginal Swab Samples and Male Urine Samples - Hardick, Andrew (American Society for Microbiology, 2006)
This study compared two assays for Trichomonas vaginalis detection, Gen-Probe's transcription-mediated amplification (TMA) assay for Trichomonas vaginalis and BTUB FRET PCR, using self-obtained clinical samples from 611 patients. Infection status was defined as two positive results by two different tests. The initial TMA assay sensitivity was 96.7%; specificity was 97.5%. The TMA assay was comparable to BTUB FRET PCR.